Keluhan Carpal Tunnel Syndrome pada Pekerja Sortasi Daun Tembakau (Studi di Gudang Restu I Koperasi Agrobisnis Tarutama Nusantara Jember) - Jawahirun Nadhifah; Ragil Ismi Hartanti; Reny Indrayani (Jurnal Kesehatan, 2018)
Abstract Recruitment of labor in tobacco industry at Jember is high and there are still many utilize manual labor. Manual labor can increase complaints from workers.There are several MSDs listed in ILO, one of which is Carpal Tunnel Syndrome (CTS). CTS can cause pain and limit the function of the wrist and hand. Sorting work is one of the jobs with a high prevalence of CTS as it requires precision and accuracy. The purpose of this research was to analyze CTS complains on leaf sorting workers in Restu I warehouse of Agribusiness Tarutama Nusantara Cooperative.This was a descriptive research with quantitative approach. The results indicates that majority of leaf tobacco leaf workers (81,7%) in Restu I Warehouse experienced CTS complaint. Respondents with age more than 40 years are 3,609 times at risk of CTS complaint. Respondents with CTS complaint were more common at age more than 40 years, who had more nutritional status categories of overweight, who had a working period of more than 4 years as tobacco leaf sorting worker at Restu I Warehouse, who had medium risk work posture, and respondents who repeat movements of the wrist more than 30 times per minute. Keywords: MSDs, Carpal Tunnel Syndrome (CTS), Tobacco Leaf Sorting